PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN - Susilawati, Enny; Hariyono, T.A; Adha, Syamsul; Norfiana, Lita; Mahyudiansyah, Mahyudiansyah (CV. Anugerah Duta Perdana, 2024)
PT JNE Pusat Banjarmasin is growing very rapidly and requires employees who have high performance. Employee performance is influenced by work discipline and work motivation. Research on the Influence of Work Discipline and Work Motivation on the Performance of PT JNE Pusat Banjarmasin Employees needs to be carried out to measure the Influence of Work Discipline and Work Motivation on the Performance of PT JNE Pusat Banjarmasin Employees using a quantitative descriptive approach. This research is an explanatory type of research, with a research population of 35 employees at PT JNE Pusat Banjarmasin. The sampling technique uses saturated or total samples. Data collection uses a questionnaire. The data analysis technique uses regression analysis. Research results based on research regression analysis show that work discipline has an effect on employee performance of 0.006 <0.05. Work motivation influences employee performance by 0.000 <0.05. If the calculated significance is <0.05, then the partial and simultaneous influence of the independent variable on the dependent variable is accepted. Thus, work discipline influences the performance of employees at PT JNE Pusat Banjarmasin. Work motivation influences employee performance at PT JNE Pusat Banjarmasin, both partially and simultaneously. It is recommended that PT JNE Pusat Banjarmasin improve work discipline and work motivation to improve employee performance even better in facing market competition and consumer behavior which continues to change and whose desires are increasingly high